Improving Students Reading Comprehension by Using Webtoon Comic Application at Professional Reading Class of English Education Study Program - Tomasoa, Imanuel P. Ch.; Que, Stella Rose; Hukom, Salmon James (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2024)
The aims of this research were to improve students reading comprehension by using webtoon comic application as a reading material. The participant of the research were students in Professional Reading Class of English Education Study Program in the academic year 2023/2024. Collaborative Action Research was used as the method in this study. The data were collected from Test and Interview. The criteria of success were 70% of students reach 75 score. The result showed that there were 10% of students (2 students) got 90 score, 5% of students (1 students) got 85 scores, 15% of students got 80 scores (3 students), and 45% of students got 75 scores (9 students). All in all, 75% of students reached 75 scores as a minimal score. It means students reading comprehension are improved after the use of webtoon comic application as reading material. Students’ response towards the use of webtoon comic application in improving their reading comprehension are fun, enjoyable, interesting and engage their motivation in reading.